Digitalisasi Instrumen Alat Ungkap Masalah (AUM) dalam Layanan Bimbingan dan Konseling: Systematic Literature Review - Su Wardani, Ni Kadek (ILIN Education Indonesia, 2025)
The main purpose of this study is to analyse the development of digitalisation of problem expression tool (AUM) instruments as well as its advantages and disadvantages to improve the effectiveness and efficiency of guidance and counselling services in schools. This research uses the Systematic Literature Review method with PRISMA (Preferred Reporting Items for Systematic Literature Review and Meta-Analysis) guidelines. Research data was obtained from research studies during the period 2017-2024. This study identified, evaluated, and synthesised 9 relevant scientific articles that had gone through the screening process using the PRISMA flowchart. Articles came from ScienceDirect, Google Scholar, Springer, Taylor & Francis Group online databases. The results of this study show that various developments of digitalisation of the Alat Ungkap Masalah (AUM) instrument, both website-based and Android-based, have been tested for feasibility and obtained a good level of satisfaction. The conclusion of this study shows that applications such as AUM PTSDL, Android-based AUM, website, and AUMDROID support the effectiveness and efficiency of counseling teachers in accelerating assessment, reducing data processing time, and developing more targeted guidance programmes.